Influence of the importance of the point and service tactical position in the shot following the return in men`s and women`s professional padel - Escudero-Tena, A.; Ibáñez, S. J.; Parraca, J. A.; Sánchez-Alcaraz, B. J.; Muñoz, D. (International Journal of Sports Science & Coaching, 2024)
The objective of this research was to analyse the shot following the return in men's and women's professional padel according to the importance of the point and the service tactical position. The type of shot following the return, importance of the shot and tactical position of the serving pair were recorded by systematic observation. A total of 2752 points (1431 men's and 1321 women's) from 69 matches played in the 2021 season of the World Padel Tour circuit were used. The results show that while men use more forehand and backhand volleys as shots following the return, women use more trays or smashes and back wall shots. In addition, while the server is the one who plays the most third shots following a straight return in men's padel (forehand and backhand volleys) and women's (forehand volleys and backhand volleys), the server's partner is the one who plays the most third shots following a lob return in the men's category (trays or smashes and back wall shots) and women's category (trays or smashes and back wall shots). Moreover, the importance of the point and the service position are parameters that affect the shot following the return in men's and women's professional padel. Thus, these findings are very novel as it is the first investigation to analyse the shot following the return in professional padel.